Copolymer and preparation method and application thereof
Through the multi-copolymerization and selective hydrogenation technology of aromatic ethylene, monoolefin and conjugated diene, copolymers with HSD and OCP structures were synthesized, and the viscosity index improver of lubricating oil at high temperatures is solved. The viscosity increase, shear resistance and low temperature flow of lubricating oil is improved at high temperatures. The problem of difficulty in taking into account both the properties has achieved excellent lubricating oil performance.
Patent Information
- Application Number
- CN202310802969.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
It is difficult for existing lubricant viscosity index improvers to achieve high-temperature viscosity enhancement effect, high-temperature shear resistance and low-temperature fluidity at the same time.
By multipolymerizing aromatic ethylene, monoolefin and conjugated diene, and selectively hydrogenating, copolymers with HSD and OCP structures are synthesized as lubricant viscosity index improver.
The copolymer has achieved a high-temperature viscosity-enhancing effect, high-temperature shear resistance and low-temperature fluidity, and is suitable for high-grade lubricating oil viscosity index improver.
Smart Images

Figure CN119219819A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating oil additives, and in particular to a copolymer and a preparation method and application thereof. Background Art
[0002] Viscosity Index Improver (VII) is an oil-soluble high molecular polymer. When added to oil products, it can improve the viscosity-temperature performance of oil products and increase the viscosity index of oil products. Modern multi-grade oils for internal combustion engines have put forward higher and higher requirements on the viscosity of lubricating oils in a wide temperature range, which makes the requirements for viscosity index improvers higher and higher. Polymers commonly used as viscosity index improvers include ethylene-propylene copolymer (OCP), hydrogenated styrene conjugated diene copolymer (HSD), methacrylates, polyisobutylene, etc.
[0003] Ethylene-propylene copolymer viscosity index improvers have good thickening ability and shear stability, strong high-temperature shear resistance, and are widely used in internal combustion engine oils. However, the low-temperature performance of this type of viscosity index improver is poor (that is, the apparent viscosity or flow performance of the lubricating oil is poor at low temperatures), and it is usually necessary to add a pour point depressant to improve its low-temperature performance. In addition, the low-temperature performance and high-temperature shear resistance of the viscosity index improver are usually contradictory. The viscosity index improver with higher thickening ability usually has a higher molecular weight, but in order to obtain better low-temperature performance, a relatively low molecular weight is usually required; thus, it is difficult to obtain a viscosity index improver with good thickening ability and shear stability, as well as good low-temperature performance. HSD-type viscosity index improvers usually have good viscosity-increasing and shear stability properties. Styrene / butadiene or isoprene copolymers are usually hydrogenated to obtain viscosity index improvers with good oxidation stability, thickening ability and shear stability. The main disadvantage is that the viscosity is low at high temperature and high shear rate.
[0004] US4116917A discloses hydrogenated butadiene / isoprene star polymers and isoprene star polymers. The chain segments generated after hydrogenation are similar to high-ethylene content OCPs, which are prone to crystallization and result in poor low-temperature performance.
[0005] CN1576359A discloses the use of linear or star-shaped random copolymers of partially hydrogenated isoprene and butadiene as lubricating oil viscosity index improvers. However, the viscosity index improvers still cannot achieve good high-temperature viscosity increasing effect, high-temperature shear resistance and low-temperature fluidity.
[0006] In summary, it is difficult for the existing various lubricating oil viscosity modifiers to simultaneously achieve ideal effects in terms of low-temperature fluidity, high-temperature viscosity-increasing effect, and high-temperature shear resistance. Summary of the invention
[0007] The purpose of the present invention is to overcome the problem that various lubricating oil viscosity modifiers in the prior art are difficult to achieve ideal effects of low-temperature fluidity, high-temperature viscosity-increasing effect and high-temperature shear resistance at the same time, and to provide a copolymer and a preparation method and application thereof. The copolymer can have good high-temperature viscosity-increasing effect, high-temperature shear resistance and low-temperature fluidity.
[0008] The inventors of the present invention unexpectedly discovered that by copolymerizing aromatic vinyl, monoolefin and conjugated diene and selectively hydrogenating, HSD and OCP copolymers can be integrated on a polymer molecular chain, thereby achieving complementary performance of HSD and OCP copolymers as lubricating oil viscosity modifiers.
[0009] In order to achieve the above object, the first aspect of the present invention provides a copolymer, the copolymer comprising a structural unit A represented by formula (1), a structural unit B and a structural unit C represented by formula (3); the structural unit B comprises a structural unit B1 represented by formula (21) and a structural unit B2 represented by formula (22);
[0010]
[0011] Wherein, R1 and R2 are each independently H or C6-C 20 substituted or unsubstituted aryl, and R1 and R2 are not H at the same time; R3, R4, R5 and R6 are each independently H or C1-C4 alkyl, and R3, R4, R5 and R6 are not H at the same time; R7 is C1-C6 alkyl.
[0012] A second aspect of the present invention provides a method for preparing a copolymer, the preparation method comprising:
[0013] In the presence of a solvent and a catalyst composition, a copolymerization reaction is carried out on a polymerizable monomer to obtain a copolymer precursor; wherein the polymerizable monomer comprises monovinyl aromatic hydrocarbon, monoolefin and conjugated diene; the monoolefin comprises ethylene and α-olefin;
[0014] The copolymer precursor is selectively hydrogenated in the presence of a hydrogenation catalyst to hydrogenate and saturate the double bonds of the structural unit C derived from the conjugated diene to obtain a copolymer.
[0015] The third aspect of the present invention provides a copolymer obtained by the aforementioned preparation method.
[0016] A fourth aspect of the present invention provides use of the aforementioned copolymer in lubricating oil.
[0017] A fifth aspect of the present invention provides a lubricating oil composition, comprising a base oil and a viscosity index improver, wherein the viscosity index improver contains the aforementioned copolymer.
[0018] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0019] The copolymer disclosed in the present invention refers to a copolymer obtained by copolymerizing and selectively hydrogenating one or more monoolefins, one or more conjugated dienes and monovinyl aromatics. Through the copolymerization of the above multi-components, a copolymer having both a HSD structure and an OCP structure in the molecular chain is obtained. The present invention can achieve the complementary performance of HSD and OCP copolymers as lubricating oil viscosity improvers, and at the same time achieve the excellent performance brought by the two structures. Therefore, the copolymer has good high-temperature viscosity-increasing effect, high-temperature shear resistance and low-temperature fluidity, and can be used as a viscosity index improver for lubricating oils. DETAILED DESCRIPTION
[0020] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] In order to achieve the above object, the first aspect of the present invention provides a copolymer, the copolymer comprising a structural unit A represented by formula (1), a structural unit B and a structural unit C represented by formula (3); the structural unit B comprises a structural unit B1 represented by formula (21) and a structural unit B2 represented by formula (22);
[0023]
[0024] Wherein, R1 and R2 are each independently H or C6-C 20 substituted or unsubstituted aryl, and R1 and R2 are not H at the same time; R3, R4, R5 and R6 are each independently H or C1-C4 alkyl, and R3, R4, R5 and R6 are not H at the same time; R7 is C1-C6 alkyl.
[0025] In the present invention, in formula (1), when R1 is H, R2 is C6-C 20 substituted or unsubstituted aryl; when R2 is H, R1 is C6-C 20 A substituted or unsubstituted aryl group.
[0026] In the present invention, in formula (3), R3, R4, R5 and R6 may be methyl groups at the same time; or, R4 is hydrogen, and R3, R5 and R6 are all methyl groups; or, R3 and R4 are all hydrogen, R5 is methyl, and R6 is ethyl; or, R3, R4, R5 are all hydrogen, and R6 is propyl, etc., which are not listed here one by one.
[0027] In the present invention, in formula (22), R7 is methyl, ethyl, propyl or butyl.
[0028] In some embodiments, the structural unit A is derived from monovinyl aromatic hydrocarbons; the structural unit B contains a structural unit B1 derived from ethylene and a structural unit B2 derived from an α-olefin; the structural unit C is derived from a conjugated diene, and the double bond in the structural unit C is saturated by hydrogenation.
[0029] In the present invention, "structural unit A derived from monovinyl aromatic hydrocarbon" refers to a structural unit formed by polymerization of monovinyl aromatic hydrocarbon. "Structural unit B1 derived from ethylene" refers to a structural unit formed by polymerization of ethylene. "Structural unit B2 derived from α-olefin" refers to a structural unit formed by polymerization of α-olefin. "Structural unit C derived from conjugated diene" refers to a structural unit formed by polymerization of conjugated diene, and the double bond in the structural unit C is saturated by hydrogenation.
[0030] The copolymer molecular chain structure disclosed in the present invention may include an A-B1-B2-C block copolymer, which is a random copolymer comprising structural unit A, structural unit B1, structural unit B2 and structural unit C, or a copolymer and an alternating copolymer comprising a mixed block and a random structure. Appropriate selection can be made according to specific application occasions. From the perspective of process simplicity, the copolymer is preferably a random copolymer.
[0031] In the present invention, the copolymer is a styrene-ethylene-α-olefin-conjugated diene copolymer, preferably a styrene-ethylene-propylene-conjugated diene copolymer.
[0032] In the present invention, the structural parameters of the copolymer can be characterized and analyzed using GPC, NMR, DSC, etc.
[0033] In the present invention, except for the double bond on the benzene ring, the remaining chemical bonds are saturated, that is, the degree of hydrogenation of the structural unit C is 100%. However, in the actual reaction process, it is difficult to avoid that a very small number of double bonds from the conjugated diene are not saturated, but the degree of hydrogenation of the structural unit C needs to be controlled to be greater than 99%, and it is also difficult to avoid that a very small number of benzene rings in the structural unit A are hydrogenated, but the degree of hydrogenation of the benzene rings in the structural unit A needs to be controlled to be less than 5%, preferably less than 2%.
[0034] In some embodiments, in the copolymer, based on the total amount of the structural unit C, the molar content of the 1,2-structure in the structural unit C is greater than 20%, preferably greater than 40%.
[0035] In the present invention, the "1,2-structure in the structural unit C" refers to a structure formed by 1,2-polymerization of a conjugated diene.
[0036] In some embodiments, the molar ratio of the structural unit A, the structural unit B and the structural unit C is 20-35:40-55:10-30.
[0037] Of all units in the copolymer of the present invention, the structural unit A derived from monovinyl aromatic hydrocarbons is preferably 20-35 mol%, the structural unit B derived from monoolefins is preferably 40-55 mol%, and the structural unit C derived from conjugated dienes is preferably 10-30 mol%.
[0038] In some embodiments, based on the total amount of the structural unit B, the molar ratio of the structural unit B1 to the structural unit B2 is 0.5-5:1, for example, 0.5:1, 0.8:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, and any value in the range consisting of any two numerical values.
[0039] In some embodiments, the content of the structural unit B1 is 20-35 mol%; the content of the structural unit B2 is 15-25 mol%.
[0040] In some embodiments, the number average molecular weight of the copolymer is 5000-200,000 g / mol, preferably 20,000-150,000 g / mol.
[0041] In some embodiments, the molecular weight distribution of the copolymer is below 2.2, preferably 0.5-2.
[0042] A second aspect of the present invention provides a method for preparing a copolymer, the preparation method comprising:
[0043] In the presence of a solvent and a catalyst composition, a copolymerization reaction is carried out on a polymerizable monomer to obtain a copolymer precursor; wherein the polymerizable monomer comprises monovinyl aromatic hydrocarbon, monoolefin and conjugated diene; the monoolefin comprises ethylene and α-olefin;
[0044] The copolymer precursor is selectively hydrogenated in the presence of a hydrogenation catalyst to hydrogenate and saturate the double bonds of the structural unit C derived from the conjugated diene to obtain a copolymer.
[0045] According to the present invention, the monoolefin refers to an unsaturated open-chain hydrocarbon containing one C=C in the molecule; the monoolefin includes ethylene and α-olefin.
[0046] In the present invention, the selective hydrogenation allows all chemical bonds except the double bond on the benzene ring to be saturated with hydrogen.
[0047] The copolymer disclosed in the present invention refers to a copolymer obtained by copolymerizing one or more monoolefins, one or more conjugated dienes and aromatic vinyl compounds. Through the copolymerization of the above multi-components, a copolymer having both HSD structure and OCP structure in the molecular chain is obtained. The excellent performance brought by the two structures is achieved at the same time. Therefore, the copolymer has good high-temperature viscosity increasing effect, high-temperature shear resistance and low-temperature fluidity, and can be used for high-grade viscosity index improver.
[0048] The copolymer of the present invention preferably has no melting point, and the low temperature performance as a lubricating oil viscosity modifier is ensured by inhibiting the crystallization of the ethylene segment.
[0049] In some embodiments, in the copolymer precursor, based on the total amount of the structural unit C derived from the conjugated diene, the molar content of the 1,2-structure in the structural unit C is greater than 20%, preferably greater than 40%.
[0050] In some embodiments, the molar ratio of the monovinylarene, the monoolefin, and the conjugated diene is 20-35:40-55:10-30.
[0051] In some embodiments, the molar ratio of ethylene to α-olefin is 1-1.5:1 based on the total amount of the monoolefin.
[0052] According to the present invention, the monovinyl aromatic hydrocarbon refers to a compound in which one hydrogen on the aromatic ring is replaced by a vinyl group. For example, the monovinyl aromatic hydrocarbon can be one or more compounds selected from the group consisting of compounds shown in Formula I.
[0053] In some embodiments, the monovinyl aromatic hydrocarbon is a compound represented by Formula I,
[0054]
[0055] In Formula I, R8 is C6-C 20 substituted or unsubstituted aryl; preferably phenyl or phenyl substituted by one or more C1-C5 alkyl groups.
[0056] In the present invention, C6-C 20Specific examples of substituted or unsubstituted aryl groups may include, but are not limited to, phenyl, o-tolyl, m-tolyl, p-tolyl, o-ethylphenyl, m-ethylphenyl, p-ethylphenyl, o-tert-butylphenyl, m-tert-butylphenyl, p-tert-butylphenyl, p-dodecylphenyl, 2,4-di-n-butylphenyl, p-n-propylphenyl, and 2,4-diethylphenyl.
[0057] In some embodiments, the monovinyl aromatic hydrocarbon is selected from one or more of styrene, 2-methylstyrene, 4-methylstyrene, 4-tert-butylstyrene, 4-methylstyrene, 3,5-diethylstyrene, 3,5-di-n-butylstyrene, 4-n-propylstyrene and 4-dodecylstyrene.
[0058] In some preferred embodiments, the monovinyl aromatic hydrocarbon is selected from one or more of styrene, 2-methylstyrene and 4-methylstyrene.
[0059] According to the present invention, α-olefins (α-olefin, Alpha Olefins) refer to monoolefins with double bonds at the ends of the molecular chains, and the molecular formula is R-CH=CH2, wherein R is an alkyl group.
[0060] In some embodiments, the α-olefin is selected from one or more of propylene, 1-butene, 1-pentene, 1-hexene and 1-octene; preferably, the α-olefin is propylene.
[0061] According to the present invention, the conjugated diene compound refers to an unsaturated chain hydrocarbon containing a conjugated double bond (i.e., -C=CC=C-) in the molecular structure, and can be various conjugated dienes commonly used in the art, without particular limitation. For example, the conjugated diene can be one or more conjugated dienes selected from C4-C8.
[0062] In some embodiments, the conjugated diene is selected from one or more of butadiene, isoprene, 1,3-pentadiene, 1,3-hexadiene and 2,3-dimethylbutadiene; preferably, the conjugated diene is selected from butadiene and / or isoprene.
[0063] In the preparation method of the present invention, the monovinyl aromatic hydrocarbon is preferably styrene, the monoolefin is preferably alpha olefin, more preferably ethylene and propylene, and the conjugated diene is preferably 1,3-butadiene and (or) isoprene. Styrene-ethylene-alpha olefin-conjugated diene copolymer hydrogenated precursor, wherein the copolymer 1,2 structure content in the unit derived from the conjugated diene compound is at least 40%. The copolymer precursor is obtained by copolymerizing styrene with ethylene, alpha olefin (propylene) and conjugated diene, and then the unsaturated double bonds in the conjugated diene are hydrogenated and saturated by selective hydrogenation to obtain a hydrogenated styrene-ethylene-alpha olefin-conjugated diene copolymer. The obtained copolymer has good high-temperature viscosity-increasing effect, high-temperature shear resistance and low-temperature fluidity, and can be used for high-grade viscosity index improvers.
[0064] In some embodiments, the copolymerization reaction conditions include: temperature of -50°C to 200°C, preferably 20-100°C; time of 0.1-6h, preferably 0.2-5h; pressure of 0.1-5MPa, preferably 0.1-2MPa.
[0065] In the present invention, the pressures are all gauge pressures.
[0066] The contact reaction of the present invention can be carried out in a solution polymerization or bulk polymerization mode. The polymerization reaction of the present invention can be a solution polymerization reaction. It should be apparent to those skilled in the art that the solvent used therein should be in a liquid state under homopolymerization conditions, and will not participate in the polymerization reaction, nor will it react with the polymer obtained by the reaction, i.e., the solvent is inert. Such solvents are obvious to those of ordinary skill in the field of polymerization, and can be easily selected. Nevertheless, for the present invention, the specific examples of the organic solvent can be, for example, one or more of benzene, toluene, ethylbenzene, xylene, pentane, n-hexane, heptane, octane and cyclohexane, preferably n-hexane, octane or heptane, and more preferably n-hexane is used as the solvent in the homopolymerization reaction of the present invention. For the polymerization reaction of the present invention, the amount of the solvent is such that the concentration of the polymer is 5-30% by weight, preferably in the range of 8-10% by weight.
[0067] According to the present invention, the above polymerization process is preferably carried out under the protection of an inert atmosphere. For example, one or more of nitrogen, helium, argon, etc. can be used to provide such an inert atmosphere.
[0068] In polyreaction of the present invention, terminator can be used to stop polyreaction after polyreaction is finished.Terminator used for this step is conventional for those skilled in the art.Usually operable terminator comprises deionized water, alcohol, acid etc.In the present invention, the terminator preferably used is one or more in isopropanol, methanol, water etc.
[0069] In particular, the olefin polymerization reaction catalyzed by the aforementioned catalyst of the present invention can achieve high catalytic efficiency while obtaining a styrene-ethylene-α-olefin-conjugated diene copolymer.
[0070] More specifically, the above preparation method can produce styrene-ethylene-α-olefin-conjugated diene copolymer with higher catalytic efficiency when the catalyst composition of the present invention is used as a catalyst. For example, the catalytic efficiency can reach 10 6 g polymer / (mol metal·h).
[0071] In some embodiments, the catalyst composition includes a main catalyst and a co-catalyst, wherein the main catalyst is a metal compound containing nitrogen and phosphine; and the co-catalyst includes an aluminum-containing compound and optionally an organic boron compound.
[0072] The catalyst composition of the present invention can adopt the catalyst composition for olefin polymerization disclosed in CN107793510A, which contains a main catalyst and a co-catalyst, wherein the main catalyst is a non-metallocene compound, and the co-catalyst contains an aluminum compound and optionally an organic boron compound. The non-metallocene compound has a structure shown in formula (II),
[0073]
[0074] Wherein, in formula (II), Y is a phosphinimine group shown in formula (III). For the specific structure, please refer to CN107793510A, which will not be repeated here.
[0075] According to a first preferred specific embodiment, the co-catalyst is an aluminum-containing compound, and the molar ratio of the main catalyst calculated as metal element to the aluminum-containing compound calculated as aluminum element is 1:(0.1-3000), preferably 1:(50-1000).
[0076] According to a second preferred specific embodiment, the co-catalyst includes an aluminum-containing compound and an organic boron compound, and the molar ratio of the main catalyst calculated as metal element, the aluminum-containing compound calculated as aluminum element and the organic boron compound calculated as boron element is 1:(5-500):(1-5), preferably 1:(5-200):(1-5).
[0077] In some embodiments, the organic boron compound is selected from at least one of tris(pentafluorophenyl)boron (B(C6F5)3), N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate ([HNMe2Ph][B(C6F5)4]), and triphenylcarbonium tetrakis(pentafluorophenyl)borate ([Ph3C][B(C6F5)4]).
[0078] According to a first preferred embodiment, the aluminum-containing compound is an alkylaluminoxane compound.
[0079] According to a second preferred specific embodiment, the aluminum-containing compound is a mixture of an alkyl aluminum compound and an alkyl aluminoxane compound; preferably, in the mixture of the alkyl aluminum compound and the alkyl aluminoxane compound, the molar ratio of the content of the alkyl aluminum compound calculated as aluminum element to the content of the alkyl aluminoxane compound calculated as aluminum element is 1:(10-500); more preferably 1:(25-300).
[0080] In some embodiments, the alkylaluminoxane compound is a compound represented by formula (IV),
[0081]
[0082] Wherein, in formula (IV), R 31 At least one selected from methyl, ethyl, n-propyl, isopropyl, 1-butyl, 2-butyl and t-butyl; t is an integer of 5-30.
[0083] Preferably, the alkylaluminum compound is selected from at least one of trimethylaluminum, triethylaluminum, tripropylaluminum, triisobutylaluminum, trihexylaluminum, dimethylaluminum chloride, diethylaluminum chloride, dipropylaluminum chloride, diisobutylaluminum chloride, dihexylaluminum chloride, methylaluminum dichloride, ethylaluminum dichloride, propylaluminum dichloride, isobutylaluminum dichloride, hexylaluminum dichloride, dimethylaluminum hydride, diethylaluminum hydride, dipropylaluminum hydride, diisobutylaluminum hydride and dihexylaluminum hydride.
[0084] The catalyst composition of the present invention may also contain other necessary additives, as long as these additives do not affect the catalytic effect of the composition. For example, the composition may contain an impurity scavenger.
[0085] In this application of the present invention, there is no particular limitation on the order and method of adding the components in the catalyst composition for olefin polymerization. The main catalyst, the cocatalyst and the optional additives may be mixed in advance and then added to the polymerization reaction, or the main catalyst, the cocatalyst and the optional additives may be added to the polymerization reaction separately. According to a preferred embodiment: the cocatalyst and the optional additives are first added to the reaction system, and then the olefin monomer is introduced, and then the main catalyst is added.
[0086] In some embodiments, the molar ratio of the catalyst composition to the polymerization monomer is (1-10)×10 -5 :1.
[0087] In some embodiments, the conditions for the selective hydrogenation include: a temperature of 40-80° C., preferably 50-70° C.; a time of 30-180 min, preferably 30-60 min; and a hydrogen partial pressure of 0.5-5 MPa, preferably 1-4 MPa.
[0088] The selective hydrogenation of the present invention has no particular limitation on the amount of hydrogen used, as long as the unsaturated double bonds in the conjugated diene segments in the copolymer can be hydrogenated and saturated. In order to ensure the smooth progress of the hydrogenation reaction, preferably, hydrogen is continuously introduced into the reaction system and the hydrogen partial pressure is maintained at 0.5-5 MPa.
[0089] In some embodiments, the hydrogenation catalyst is selected from one or more of biscyclopentadienyldi-p-tolyltitanium, bis(cyclohexyl-cyclopentadienyl)di-p-tolyltitanium, biscyclopentadienyldi-p-tolyltitanium, diphenyldiphenyltitanocene, di-p-phenyldititanocene, di-m-tolyldititanocene, bis(methyl-cyclopentadienyl)di-p-tolyltitanium and bis(methyl-cyclopentadienyl)diphenyltitanium.
[0090] The hydrogenation catalyst in the present invention can be the metallocene catalyst disclosed in CN1373008A, which will not be described in detail here.
[0091] The hydrogenation catalyst can be introduced into the reaction system in the form of a solution. The solvent in the hydrogenation catalyst solution can be, for example, one or more of straight-chain alkanes (such as pentane, hexane, heptane, octane, etc.), saturated cycloalkanes (such as cyclohexane), benzene, toluene and polar solvents (such as tetrahydrofuran, ether, dioxane, etc.). The concentration of the hydrogenation catalyst solution can be, for example, 0.5-10% by weight.
[0092] In some embodiments, the amount of the hydrogenation catalyst used is 0.05-0.5 mmol relative to 100 g of the copolymer precursor.
[0093] The third aspect of the present invention provides a copolymer obtained by the preparation method described in the second aspect.
[0094] The fourth aspect of the present invention provides use of the copolymers described in the first and third aspects in lubricating oil.
[0095] A fifth aspect of the present invention provides a lubricating oil composition, comprising a base oil and a viscosity index improver, wherein the viscosity index improver contains the copolymer described in the first and third aspects.
[0096] In some embodiments, the content of the viscosity index improver is 0.1-2 wt % based on the total amount of the lubricating oil composition.
[0097] The present invention is described in detail below by way of examples, but the protection scope of the present invention is not limited to the following description.
[0098] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0099] In the following embodiments,
[0100] The molecular weight and molecular weight distribution index (M w / M n ) was determined using a Cirrus liquid gel permeation chromatograph produced by Agilent, and the chromatographic column model used was TSKgel GMH6-HT. The mobile phase was trichlorobenzene, the flow rate was 1 mL / min; the sample solution concentration was 0.1 mg / mL, the injection volume was 200 μL; the test temperature was 150°C; and monodistributed polystyrene was used as the standard sample.
[0101] The nuclear magnetic resonance hydrogen spectrum test was conducted using an AVANCE DRX 400 MHz nuclear magnetic resonance instrument purchased from Brune, using deuterated o-dichlorobenzene as solvent and tetramethylsilane (TMS) as an internal standard.
[0102] The melting point and glass transition temperature were measured using a Mettler Toledo DSC 822e differential scanning calorimeter with a heating rate of 10°C / min, a temperature range of -100 to 200°C, a nitrogen atmosphere, and a flow rate of 50 mL / min.
[0103] Catalytic efficiency refers to the mass of polymer obtained per unit molar amount of Mt and is expressed in units of g polymer / (mol metal·h).
[0104] Example 1
[0105] Step 1: Synthesis of copolymer precursor
[0106] In a glove box, a magnetic stirrer was placed in a 50 mL round-bottom flask, and 5 μmol of (2,6-dimethylphenoxy)tri-tert-butylphosphinimine titanium dichloride and 5 μmol of (pentafluorophenyl) borate ([Ph3C][B(C6F5)4]) and 0.26 mmol of triisobutylaluminum were added, and the mixture was stirred and dissolved in 10 ml of toluene to obtain a catalyst solution, which was then loaded into a small tank for adding the main catalyst. 0.5 mmol of methylaluminoxane (MAO) was added to the small tank for adding the co-catalyst. The mixture was taken out and connected to the polymerization system. After the 0.5 L autoclave was replaced with inert gas, 176 g of toluene, 95.7 g (0.92 mol) of styrene, 24.9 g (0.46 mol) of co-catalyst and butadiene were added in sequence, and a pre-mixed mixture of ethylene / propylene / hydrogen (ethylene / propylene / hydrogen = 5:1:0.05 molar ratio) was added until the pressure of the reactor reached 0.8 MPa. Saturation for a period of time. The temperature was raised to 60°C, and the main catalyst solution was added to start the reaction. The pressure of the polymerization reactor was kept constant during the reaction. The reaction was stopped after 20 minutes of reaction. The reaction solution was added to ethanol containing hydrochloric acid. The polymer was filtered and washed, and dried in a vacuum oven at 50°C to constant weight to obtain a copolymer precursor.
[0107] Step 2: Hydrogenation of copolymer precursor
[0108] 10 g of the copolymer precursor obtained in the above step 1 was dissolved in 150 g of hexane, added to a 0.5 L pressure-resistant hydrogenation reactor, 0.1 mmol of n-butyl lithium was added, hydrogen was introduced and stirred for 30 minutes, 10 ml of 5 μmol of bis(phenyl-cyclopentadienyl)di-m-tolyltitanium hexane solution was added, and the mixture was reacted at 70° C. for 60 minutes under a hydrogen pressure of 1.5 MPa. The reaction solution was added to ethanol containing hydrochloric acid, the polymer was filtered and washed, and dried in a vacuum oven at 50° C. to constant weight to obtain a copolymer product.
[0109] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0110] Example 2
[0111] Step 1: Synthesis of copolymer precursor
[0112] In a glove box, a magnetic stirrer was placed in a 50 mL round-bottom flask, and 5 μmol of (2,6-di-tert-butylphenoxy)tri-tert-butylphosphinimine titanium dichloride and 5 μmol of (pentafluorophenyl) borate ([Ph3C][B(C6F5)4]) and 0.26 mmol of triisobutylaluminum were added, and the mixture was stirred and dissolved in 10 ml of toluene to obtain a catalyst solution, which was then loaded into a small tank for adding the main catalyst. 0.5 mmol of methylaluminoxane (MAO) was added to the small tank for adding the co-catalyst. The mixture was taken out and connected to the polymerization system. After the 0.5 L autoclave was replaced with inert gas, 176 g of toluene, 8.32 g (0.08 mol) of styrene, 49.8 g (0.92 mol) of the co-catalyst and butadiene were added in sequence, and the pre-mixed ethylene / propylene (ethylene / propylene = 5:1 molar ratio) mixed gas was added until the pressure of the reactor reached 0.8 MPa. Saturated for a period of time. The temperature was raised to 60°C, and the main catalyst was added to start the reaction. The pressure of the polymerization reactor was kept constant during the reaction. The reaction was stopped after 20 minutes. The reaction solution was added into ethanol containing hydrochloric acid. The polymer was filtered and washed, and dried in a vacuum oven at 50°C to constant weight to obtain a copolymer precursor.
[0113] The copolymer precursor was hydrogenated according to the method of step 2 of Example 1.
[0114] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0115] Example 3
[0116] According to the method of Example 1, the difference is that 2.08g (0.02mol) of styrene and 40g (0.74mol) of butadiene are added to the pre-mixed ethylene / propylene (ethylene / propylene = 5:1 molar ratio) mixed gas until the pressure of the reactor reaches 0.8MPa. Saturate for a period of time. Heat to 60°C, add the main catalyst to start the reaction. Keep the pressure of the polymerization reactor unchanged during the reaction. Stop the reaction after 20 minutes of reaction. Add the reaction solution into ethanol containing hydrochloric acid. Filter and wash the polymer, and dry it in a vacuum oven at 50°C to constant weight to obtain a copolymer precursor.
[0117] The copolymer precursor was hydrogenated according to the method of step 2 of Example 1.
[0118] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0119] Example 4
[0120] The method of Example 1 was followed, except that 21.8 g (0.21 mol) of styrene and 75.2 g (1.39 mol) of butadiene were used, and the hydrogenation of the copolymer precursor was carried out according to the method of step 2 of Example 1.
[0121] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0122] Example 5
[0123] The method of Example 1 was followed, except that 54.1 g (0.52 mol) of styrene and 99.9 g (1.85 mol) of butadiene were used, and the hydrogenation of the copolymer precursor was carried out according to the method of step 2 of Example 1.
[0124] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0125] Example 6
[0126] The method of Example 1 is followed, except that 54.1 g (0.52 mol) of styrene and 49.8 g (0.92 mol) of butadiene are added to a pre-mixed ethylene / propylene (ethylene / propylene = 1:1 molar ratio) mixed gas until the pressure of the reactor reaches 0.8 MPa. Saturate for a period of time. Heat to 60°C, add the main catalyst to start the reaction. Keep the pressure of the polymerization reactor unchanged during the reaction. Stop the reaction after 20 minutes of reaction. Add the reaction solution into ethanol containing hydrochloric acid. Filter and wash the polymer, and dry it in a vacuum oven at 50°C to constant weight to obtain a copolymer precursor.
[0127] The copolymer precursor was hydrogenated according to the method of step 2 of Example 1.
[0128] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0129] Example 7
[0130] A copolymer precursor was obtained by following the method of Example 6 except that 33.3 g (0.32 mol) of styrene and 75.0 g (1.387 mol) of butadiene were used.
[0131] The copolymer precursor was hydrogenated according to the method of step 2 of Example 1.
[0132] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0133] Example 8
[0134] A copolymer precursor was obtained by following the method of Example 6 except that 24.9 g (0.24 mol) of styrene and 49.9 g (0.924 mol) of butadiene were used.
[0135] The copolymer precursor was hydrogenated according to the method of step 2 of Example 1.
[0136] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0137] Example 9
[0138] A copolymer precursor was obtained by following the method of Example 6 except that 124.8 g (1.2 mol) of styrene and 49.9 g (0.924 mol) of butadiene were used.
[0139] The copolymer precursor was hydrogenated according to the method of step 2 of Example 1.
[0140] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0141] Example 10
[0142] The method of Example 9 is followed, except that a pre-mixed ethylene / propylene (ethylene / propylene = 0.5:1 molar ratio) mixed gas is added until the reactor pressure reaches 0.8 MPa. Saturate for a period of time. Heat to 60°C, add the main catalyst to start the reaction. Keep the pressure of the polymerization reactor unchanged during the reaction. Stop the reaction after 20 minutes of reaction. Add the reaction solution into ethanol containing hydrochloric acid. Filter and wash the polymer, and dry it in a vacuum oven at 50°C to constant weight to obtain a copolymer precursor.
[0143] The copolymer precursor was hydrogenated according to the method of step 2 of Example 1.
[0144] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0145] Embodiment 11
[0146] A copolymer precursor was obtained by following the method of Example 10 except that 24.96 g (0.24 mol) of styrene and 75.02 g (1.387 mol) of butadiene were used.
[0147] The copolymer precursor was hydrogenated according to the method of step 2 of Example 1.
[0148] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0149] Example 12
[0150] A copolymer precursor was obtained by following the method of Example 10 except that 95.7 g (0.92 mol) of styrene and 24.9 g (0.462 mol) of butadiene were used.
[0151] The copolymer precursor was hydrogenated according to the method of step 2 of Example 1.
[0152] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0153] Example 13
[0154] A copolymer precursor was obtained by following the method of Example 10, except that styrene was used in an amount of 8.32 g (0.08 mol) and 75.02 g (1.387 mol).
[0155] The copolymer precursor was hydrogenated according to the method of step 2 of Example 1.
[0156] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0157] Comparative Example 1
[0158] Step 1: Synthesis of copolymer precursor
[0159] In a glove box, place a magnetic stirrer in a 50mL round-bottom flask, add 5μmol of (2,6-dimethylphenoxy)tri-tert-butylphosphinimine titanium dichloride and 5μmol of (pentafluorophenyl) borate ([Ph3C][B(C6F5)4]) and 0.26mmol of triisobutylaluminum, stir and dissolve in 10ml of toluene to obtain a catalyst solution, which is loaded into a small tank for adding the main catalyst. Add 0.5mmol of methylaluminoxane (MAO) to the small tank for adding the co-catalyst. Take it out and connect it to the polymerization system. After replacing the inert gas in the 0.5L autoclave, add 176g of toluene, 95.7g (0.92mol) of styrene, 24.9g (0.46mol) of the co-catalyst and butadiene in sequence, heat to 60°C, and add the main catalyst solution to start the reaction. Keep the pressure of the polymerization autoclave unchanged during the reaction. Stop the reaction after 20 minutes of reaction. Add the reaction solution to ethanol containing hydrochloric acid. The polymer was filtered and washed, and dried in a vacuum oven at 50° C. to a constant weight to obtain a copolymer precursor.
[0160] Step 2: Hydrogenation of copolymer precursor
[0161] 10 g of the copolymer precursor obtained in the above step 1 was dissolved in 150 g of hexane, added to a 0.5 L pressure-resistant hydrogenation reactor, 0.1 mmol of n-butyl lithium was added, hydrogen was introduced and stirred for 30 minutes, 10 ml of 5 μmol of bis(phenyl-cyclopentadienyl)di-m-tolyltitanium hexane solution was added, and the mixture was reacted at 70° C. for 60 minutes under a hydrogen pressure of 1.5 MPa. The reaction solution was added to ethanol containing hydrochloric acid, the polymer was filtered and washed, and dried in a vacuum oven at 50° C. to constant weight to obtain a hydrogenated butadiene-styrene copolymer product.
[0162] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0163] Comparative Example 2
[0164] In a glove box, a magnetic stirrer was placed in a 50 mL round-bottom flask, and 5 μmol of (2,6-dimethylphenoxy)tri-tert-butylphosphinimine titanium dichloride and 5 μmol of (pentafluorophenyl) borate ([Ph3C][B(C6F5)4]) and 0.26 mmol of triisobutylaluminum were added, and the mixture was stirred and dissolved in 10 ml of toluene to obtain a catalyst solution, which was then loaded into a small tank for adding the main catalyst. 0.5 mmol of methylaluminoxane (MAO) was added to the small tank for adding the co-catalyst. The mixture was taken out and connected to the polymerization system. After the 0.5 L autoclave was replaced with inert gas, 176 g of toluene was added, and a pre-mixed mixture of ethylene / propylene / hydrogen (ethylene / propylene / hydrogen = 5:1:0.05 molar ratio) was added until the reactor pressure reached 0.8 MPa. Saturated for a period of time. The temperature was raised to 60 ° C, and the main catalyst solution was added to start the reaction. The pressure of the polymerization reactor was kept constant during the reaction. The reaction was stopped after 20 minutes of reaction. The reaction solution was added into ethanol containing hydrochloric acid. The polymer was filtered, washed, and dried in a vacuum oven at 50° C. to constant weight to obtain an ethylene-propylene copolymer.
[0165] The amounts of various raw materials are shown in Table 1, and the test results of the copolymer products are shown in Table 2.
[0166] Table 1 Raw materials and dosage corresponding to each embodiment
[0167]
[0168] Table 2 Results of styrene-ethylene-α-olefin-conjugated diene copolymerization
[0169]
[0170]
[0171] In Table 2, Tg is the glass transition temperature, Tm is the melting temperature, and Bd-1,2 is the structural unit formed by 1,2-polymerization.
[0172] The present invention also provides a lubricating oil using the copolymer as a viscosity index improver.
[0173] According to the present invention, in order to better exert the superior properties of the viscosity index improver in the lubricating oil, preferably, the content of the viscosity index improver is 0.1-2% by weight.
[0174] According to the present invention, the lubricating oil is not particularly limited and may be any conventional lubricating oil in the art. The viscosity index improver of the present invention is more suitable for treating natural mineral oil and / or synthetic lubricating oil.
[0175] The copolymers obtained in Examples 5, 6, 9, 13 and Comparative Examples 1-2 were mixed with base oil (150SN lubricant purchased from Yanshan Petrochemical Company) at a weight ratio of 1:99 to obtain lubricants VI-1, VI-2, VI-3, VI-4, DI-1 and DI-1, respectively. The obtained lubricants were tested for performance in the following manners. The results are shown in Tables 3-5.
[0176] Kinematic viscosity refers to the ratio of the absolute viscosity of the lubricating oil to the density of the lubricating oil at the same temperature, in mm 2 / s, the kinematic viscosity of the solution was tested by a rotational rheometer (Thermo Scientific HAAKE RheoStress 6000) according to GB265-88, and the test temperature was 100°C.
[0177] The viscosity index refers to the viscosity index, which indicates the degree to which the viscosity of the lubricating oil changes with temperature. VI = [(LU) / (LH)] × 100, is calculated by testing the kinematic viscosity of the solution using a rotational rheometer (Thermo Scientific HAAKE RheoStress 6000).
[0178] Thickening ability refers to the difference in viscosity between a base oil to which a viscosity index improver is added and a base oil to which a viscosity index improver is not added. It is determined based on the difference in kinematic viscosity of the lubricating oil at 100°C.
[0179] Shear stability index (SSI) refers to the ability of a polymer to increase viscosity under shear conditions; SSI = 100% × (Vb-Va) / (Vb-V0); where Vb is the viscosity of the lubricant before shearing, Va is the viscosity of the lubricant after shearing, and V0 is the viscosity of the base oil.
[0180] High temperature and high shear viscosity refers to the apparent viscosity of lubricating oil measured under high temperature and high shear rate conditions.
[0181] Pour point refers to the lowest temperature at which lubricating oil can flow during the process of rising temperature, expressed in °C; it is determined according to the method of GB / T3535.
[0182] Table 3 High temperature viscosity enhancement effect
[0183]
[0184] Note: “—” means the base oil itself has no thickening ability, and this item is 0.
[0185] It can be seen from the data in Table 3 that the viscosity index improver of the present invention has a high viscosity index and a strong thickening ability for lubricating oil base oil.
[0186] Table 4 High temperature shear resistance
[0187]
[0188] It can be seen from the data in Table 4 that the shear stability index SSI of the viscosity index improver of the present invention can reach <15, and the shear stability is good.
[0189] Table 5 Low temperature fluidity
[0190]
[0191] It can be seen from the data in Table 5 that the viscosity index improver of the present invention has a low low-temperature viscosity, which is beneficial for the use of lubricating oil in a low-temperature environment.
[0192] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A copolymer, characterized in that The copolymer comprises a structural unit A represented by formula (1), a structural unit B and a structural unit C represented by formula (3); the structural unit B comprises a structural unit B1 represented by formula (21) and a structural unit B2 represented by formula (22); Wherein, R1 and R2 are each independently H or C6-C 20 substituted or unsubstituted aryl, and R1 and R2 are not H at the same time; R3, R4, R5 and R6 are each independently H or C1-C4 alkyl, and R3, R4, R5 and R6 are not H at the same time; R7 is C1-C6 alkyl.
2. The copolymer according to claim 1, wherein The structural unit A is derived from monovinyl aromatic hydrocarbon; the structural unit B contains a structural unit B1 derived from ethylene and a structural unit B2 derived from α-olefin; the structural unit C is derived from a conjugated diene, and the double bond in the structural unit C is saturated by hydrogenation.
3. The copolymer according to claim 1 or 2, wherein In the copolymer, based on the total amount of the structural unit C, the molar content of the 1,2-structure in the structural unit C is 20% or more, preferably 40% or more.
4. The copolymer according to any one of claims 1 to 3, wherein The molar ratio of the structural unit A, the structural unit B and the structural unit C is 20-35:40-55:10-30; Preferably, based on the total amount of the structural unit B, the molar ratio of the structural unit B1 to the structural unit B2 is 0.5-5:
1.
5. The copolymer according to any one of claims 1 to 4, wherein The number average molecular weight of the copolymer is 5000-200,000 g / mol, preferably 20,000-150,000 g / mol; And / or, the molecular weight distribution of the copolymer is below 2.2, preferably 0.5-2.
6. A method for preparing a copolymer, characterized in that: The preparation method comprises: In the presence of a solvent and a catalyst composition, a copolymerization reaction is carried out on a polymerizable monomer to obtain a copolymer precursor; wherein the polymerizable monomer comprises monovinyl aromatic hydrocarbon, monoolefin and conjugated diene; the monoolefin comprises ethylene and α-olefin; The copolymer precursor is selectively hydrogenated in the presence of a hydrogenation catalyst to hydrogenate and saturate the double bonds of the structural unit C derived from the conjugated diene to obtain a copolymer.
7. The preparation method according to claim 6, wherein: In the copolymer precursor, based on the total amount of the structural unit C derived from the conjugated diene, the molar content of the 1,2-structure in the structural unit C is greater than 20%, preferably greater than 40%.
8. The preparation method according to claim 6 or 7, wherein: The molar ratio of the monovinyl aromatic hydrocarbon, the monoolefin and the conjugated diene is 20-35:40-55:10-30; Preferably, the molar ratio of ethylene to α-olefin is 1-1.5:1 based on the total amount of the monoolefin.
9. The preparation method according to any one of claims 6 to 8, wherein: The monovinyl aromatic hydrocarbon is a compound represented by formula I, In Formula I, R8 is C6-C 20 a substituted or unsubstituted aryl group; and / or, the α-olefin is selected from one or more of propylene, 1-butene, 1-pentene, 1-hexene and 1-octene; And / or, the conjugated diene is selected from one or more of butadiene, isoprene, 1,3-pentadiene, 1,3-hexadiene and 2,3-dimethylbutadiene; preferably, the conjugated diene is selected from butadiene and / or isoprene.
10. The preparation method according to any one of claims 6 to 9, wherein: The conditions of the copolymerization reaction include: temperature of -50°C to 200°C, preferably 20-100°C; time of 0.1-6h, preferably 0.2-5h; pressure of 0.1-5MPa, preferably 0.1-2MPa.
11. The preparation method according to any one of claims 6 to 10, wherein: The catalyst composition comprises a main catalyst and a co-catalyst, wherein the main catalyst is a metal compound containing nitrogen and phosphine; the co-catalyst comprises an aluminum compound and an optional organic boron compound; Preferably, the molar ratio of the catalyst composition to the polymerization monomer is (1-10)×10 -5 :
1.
12. The preparation method according to any one of claims 6 to 11, wherein: The selective hydrogenation conditions include: temperature of 40-80°C, preferably 50-70°C; time of 30-180 min, preferably 30-60 min; hydrogen partial pressure of 0.5-5 MPa, preferably 1-4 MPa; And / or, the hydrogenation catalyst is selected from one or more of biscyclopentadienyldi-p-tolyltitanium, bis(cyclohexyl-cyclopentadienyl)di-p-tolyltitanium, biscyclopentadienyldi-p-tolyltitanium, diphenyldiphenyltitanocene, di-p-phenyldititanocene, di-m-tolyldititanocene, bis(methyl-cyclopentadienyl)di-p-tolyltitanium and bis(methyl-cyclopentadienyl)diphenyltitanium; Preferably, the amount of the hydrogenation catalyst used is 0.05-0.5 mmol relative to 100 g of the copolymer precursor.
13. The copolymer obtained by the preparation method according to any one of claims 6 to 12.
14. Use of the copolymer according to any one of claims 1 to 5 and 13 in lubricating oil.
15. A lubricating oil composition, characterized in that: The lubricating oil composition comprises a base oil and a viscosity index improver, wherein the viscosity index improver comprises the copolymer according to any one of claims 1 to 5 and 13; Preferably, the content of the viscosity index improver is 0.1-2 wt % based on the total amount of the lubricating oil composition.
Citation Information
Patent Citations
Lubricating oils, lubricating oil compositions, and fuel oil compositions
CA2242918A1
Viscosity index improver for recombined type lubrication oil
CN103468347A
Lubricating-oil viscosity index improver and preparation method thereof
CN104342231A
